Pāshā : sam̆sāra prasiddha likhārīāṃ dīāṃ coṇawīāṃ kahāṇīāṃ - Shāda, Je. Aisa (SAMP early 20th-century Indian books project, 1940)
Selection of short stories by foreign authors, translated into Panjabi.